Teaching, technology and test scores: The impact of personal computers on student performance in primary school - Caroline King Barnard Hall; Martin Lundin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
The closing of schools and shift to remote teaching during the COVID-19 pandemic has accelerated the use of digital technology in education. Many schools today provide personal computers not only to older students, but also in primary school. There is little credible evidence on how one-to-one (1:1) computer programs affect learning outcomes among younger pupils. We investigate how 1:1 computer technology impacts student performance in primary school in Sweden, using data from an expansion of 1:1 programs that took place before the pandemic. Using a staggered difference-in-differences design, we examine impacts on student performance on standardized tests in language and math in 6th grade. We find no important effects on these learning outcomes on average, but a positive effect on test scores in Swedish and English among students with highly educated parents. Moreover, the results indicate a positive effect in Swedish in schools that received additional financial support for implementing 1:1 technology. Nevertheless, all positive impacts in subgroups appear to be rather small, amounting to 0.01-0.03 SD per semester of 1:1 exposure.
Keywords: I21; I24; 330; Technology; computers; one-to-one programs; student performance